Phylogenetic structure of wildlife assemblages shapes patterns of infectious livestock diseases in Africa. (18th March 2019) - Wang, Yingying X. G.; Matson, Kevin D.; Prins, Herbert H. T.; Gort, Gerrit; Awada, Lina; Huang, Zheng Y. X.; de Boer, Willem F.
Abstract: Host species diversity can affect disease risk, but the precise nature of this effect is disputed. To date, most studies on the diversity–disease relationships have focused on host species richness and single diseases, ignoring phylogenetic diversity and disease richness. We first evaluated the effects of wildlife assemblage variables (i.e. species richness of wild ungulates and carnivores, phylogenetic structure) and livestock host density on the regional occurrence of 19 individual livestock diseases in Africa. We then explored the relationships between wildlife assemblage variables and the total disease burden (measured as disease richness) at regional scale across the entire continent of Africa. Our results suggest that wild ungulate and carnivore species richness had a positive relationship with disease richness, but no relationship with disease occurrence. When controlling for host species richness, standardized phylogenetic divergence was negatively correlated with both disease richness and disease occurrence while standardized phylogenetic richness was positively correlated with disease occurrences. Our results suggest that the phylogenetic structure of the surrounding wildlife assemblage can shape patterns of livestock diseases in Africa. Species richness alone is apparently inadequate for analyses of disease–diversity relationships, and this shortfall might partly account for current disagreements over the importance of the dilution effect. Future studies on this topic should strive to include parameters that take host phylogeny into account. A plain language summary is available for this article. Abstract : Plain Language Summary